Korelasi Perencanaan Dengan Sistem Penganggaran Dalam Pendidikan - Nunung Nurlina; Riduwan Riduwan (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
This research was prepared with the aim of explaining the correlation between planning and budgeting systems in education. This writing uses qualitative methods. The results of this research conclude that the planning and budgeting systems are closely related. With good budget planning, you can certainly realize your mutually desired educational goals.